Biodegradation of monocrotophos by indigenous soil bacterial isolates in the presence of humic acid, Fe (III) and Cu (II) ions. (September 2021) - Singh, Simranjeet; Singh, Joginder; Ramamurthy, Praveen C.; Kumar, Vijay; Bhardwaj, Sonali; Garg, Vinod Kumar
Abstract: Three bacteria, namely Streptomyces sp. MCP1, Rhizobium leguminosarum MCP2 and Bacillus subtilis MCP3, isolated from an arable field, have been used for the biodegradation of monocrotophos (MCP). The bacterial strains were characterized based on the 16S rRNA gene sequence. MCP was subjected to biological degradation in two ways, i.e., with or without using Fe(III), Cu(II), and humic acid (HA). The isolates were capable of degrading MCP in an order: MCP2 ( Bacillus subtilis ) > MCP1 ( Streptomyces sp.) > MCP3 ( Rhizobium leguminosarum ). With the application of Cu(II) and Fe(III), the biodegradation of MCP was from 83 to 92% and 78 to 87%, respectively. Altogether, under different conditions, the order of inhibition of MCP biodegradation was apparently as HA > Fe(III) > Cu(II). Mass spectrometric and UV–visible spectrophotometric results showed that MCP biodegradation's only pathway included major intermediatory metabolites (E) 4-amino-4-oxobut-2-en-2-yl dimethyl phosphate, dimethyl phosphate, methyl hydrogen phosphate and phosphonate. Graphical abstract: Unlabelled Image Highlights: Isolated bacterial strains utilized 75–92% of monocrotophos. The half-life period varied from 7.9 to 12.54 days. Monocrotophos biodegradation inhibition order was HA > Cu(II) > Fe(III). Monocrotophos degradation enhanced by de-methylation and dehydration